What causes the abrupt changes in the light curve of a GEO satellite?. (December 2018) - Wang, Yang; Du, Xiaoping; Zhao, Jiguang; Yin, Zhiyong; Song, Yishuo
Abstract: In the light curve of the geostationary earth orbit satellite (GEOS), there are 3 abrupt changes (AC) that are commonly to be seen. One of the AC that appears a peak near zero phase angle has been proved the specular reflection of solar panels leading to the phenomenon. However, the reasons of another two AC produced in the light curve are still unknown. In this paper, we proposed an advanced light curve model of GEOS and theoretically explained these unknown abrupt changes. Through calculating the satellite TDRS-8's light curve and comparing its actual observation, the proposed model is verified and the causes of the unknown abrupt changes are illustrated. The importance and purpose of this discovery are also emphasized at the end of the paper. Highlights: An advanced light curve model is proposed and the simulation light curve is more in line with the actual measurement. The proposed model can determine visible facets of a space object of any shapes. The proposed model take the effects of perturbation forces and solar panel rotation into consideration. The reasons for the abrupt change in the light curve of satellite TDRS-8 are discovered.